KUALlTAS PELAYANAN DlNAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PlNTU DALAM lZlN PENGELOLAAN TEMPAT PARKlR MELALUl APLlKASl GAMPlL FOR PUBLlC Dl KOTA BANDUNG (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2023)
The pur pose of th is study is to find out, analyze the extent of t he quality of t he Service Office of lnvestment and One Stop lntegrated Services in the Parking Plant Mana gement Permit through the Gampil for Public Application in Bandung. Thls study usess a desscriptive method with a qualitative approach w here this data is collected by observation, interviews and recording using descriptive methods with a qualitative approach. The tec hnique of determ ining the informant in this study is to use purposive techniques. The results of the st udy show that th ere are deficiencies that must be corrected, in the tangible dimension or physical evidence that there is a deficiency in information to the public about the licensing flow. Reliability or deficiency capabilities in applications that often experience problems when entering the queue for the application of the Gampil for Public Application. Responsiveness, there are deficiencies in the findings of more than 7 days of service and not in accordance with those determined by the standard operating procedures. Assurance in providing guarantees has been effectively seen from the apparatus providing guarantees in service to the community. Empathy in the service of the community has been effectively carried out from the ability of the apparatus in serving and respecting every community related to the Gampil for Public application service.